A Low‐Sulfidation Epithermal Mineralization in the River Reef Zone, the Poboya Prospect, Central Sulawesi, Indonesia: Vein Textures, Ore Mineralogy, and Fluid Inclusions. Issue 4 (21st June 2019) - Rivai, Tomy Alvin; Yonezu, Kotaro; Syafrizal,; Sanematsu, Kenzo; Kusumanto, Damar; Imai, Akira; Watanabe, Koichiro
Abstract: The Poboya Prospect lies along the North Northwest ‐ South Southeast Palu‐Koro Fault Zone in the central part of the West Sulawesi Arc. The geology of the area consists of the Palu Metamorphic Complex overlain by the Paleogene‐Neogene Tinombo Formation of volcanosedimentary rocks, the Celebes Molasse sediment, and Late Cenozoic granitic rocks. Petrography, scanning electron microscope with energy‐dispersive spectrometry (SEM‐EDS), electron probe microanalyzer (EPMA), and fluid inclusion microthermometry were carried out to examine vein textures, ore mineralogy, and characteristics of the ore‐forming fluid responsible for mineralization in the River Reef Zone, the Poboya Prospect. Textures of quartz‐carbonate veins in the River Reef Zone include massive micro‐comb, moss, colloform, crustiform, mosaic, feathery, flamboyant, lattice bladed, ghost bladed, parallel bladed, and saccharoidal textures representing primary growth, recrystallization, and replacement. The homogenization temperature and fluid salinity are 240–250°C and 0.3–0.7 wt% NaCl eq., respectively. Ore minerals precipitated in the early stage consist of electrum, naumannite‐aguilarite, chalcopyrite, pyrite, marcasite, sphalerite, and pyrrhotite. Apart from pyrrhotite, these ore minerals were also precipitated in the late stage along with selenopolybasite, freibergite, argyrodite, pyrargyrite, and galena. Selenium more preferably occurs as the crystallographic replacement of sulfur in naumannite‐aguilarite, argyrodite, pyrargyrite, selenopolybasite, and freibergite instead of as independent selenide minerals. The low‐sulfidation epithermal deposit in the River Reef Zone, the Poboya Prospect, illustrates the potential of the West Sulawesi Arc, particularly along the Palu‐Koro Fault Zone, to host epithermal gold mineralization. Abstract : Veins in the River Reef Zone show primary, recrystallization, and replacement textures and contain ore minerals precipitated in the early and late stages. The ore‐forming fluid was 240–250°C and 0.3–0.7 wt% NaCl eq. Selenium found in the ore minerals replaced sulfur in the crystal structures of the minerals.